Implementation of Lean Six Sigma Method in Cross Circuit in Sub Assy Area to Improve Product Quality - Sulistiyowati, Wiwik; Sandari, Malik; Jakaria, Ribangun Bamban (International Journal of Engineering and Technology, 2018)
The purpose of this study is to identify activities that are not value added (waste) and know the level of disability of cross circuit products. The method used in this research is quantitative with lean six sigma concept approach. The result of this research is the highest waste type is the waste defect with the value of 4.7, and the level of disability is found on a cross circuit of 870 DPMO (Defect per Million Opportunity) or 4,653 sigmas. It shows that the sigma value found in cross circuit product in sub assy area can be said good because DPMO value is close to sigma number. Based on these results, then for further research can identify potential interference in the process of a cross circuit in sub assy area by using FMECA (Failure Mode Effect Critically Analysis) method and develop an operational standard procedure to reduce variation in doing the job Â